The Impact of Platform Governance and Seller Support on Seller Performance on Marketplace Platforms in West Java - Paramita Andiani; Rani Eka Arini; Aya Sofia Diaz (West Science Interdisciplinary Studies, 2026)
The rapid expansion of online marketplaces has created significant opportunities for entrepreneurs and small businesses to access broader markets and improve business performance. However, the ability of sellers to achieve sustainable performance is influenced by the quality of platform management and the support mechanisms provided by marketplace operators. This study aims to examine the impact of platform governance and seller support on seller performance among online marketplace sellers in West Java. This research employed a quantitative approach using a survey method involving 125 online marketplace sellers as respondents. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The data analysis included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that both platform governance and seller support have a positive and significant effect on seller performance. Platform governance shows a significant influence, demonstrating that transparent policies, transaction security, and fair platform management contribute to improved seller outcomes. Meanwhile, seller support has a stronger positive influence, indicating that training programs, technical assistance, marketing support, and communication facilities play important roles in enhancing sellers’ capabilities. Furthermore, the coefficient of determination (R² = 0.520) shows that platform governance and seller support explain 52.0% of the variation in seller performance. This study highlights that marketplace providers should develop integrated governance systems and comprehensive seller support programs to strengthen seller competitiveness and promote sustainable digital commerce development, particularly in the West Java marketplace ecosystem.